Neoadjuvant and postoperative chemotherapy with paclitaxel plus cisplatin for the treatment of FIGO stage IB cervical cancer in pregnancy - Kong, Tae-Wook (Obstet Gynecol Sci, 2014)
Cervical cancer is one of the most common malignancy diagnosed during pregnancy. The experience of the use of neoadjuvant chemotherapy (NACT) with paclitaxel plus cisplatin during pregnancy is limited. Three pregnant women with International Federation of Gynecology and Obstetrics (FIGO) stage IB cervical cancer received NACT with paclitaxel plus cisplatin until fetal lung maturity, and then underwent cesarean delivery and radical hysterectomy. Two of our patients had intermediate pathologic risk factors, and received adjuvant chemotherapy with the same regimen used in NACT. All patients did not have any evidence of disease recurrence for follow-up of 3, 4, and 8 years, respectively. NACT with paclitaxel plus cisplatin followed by radical hysterectomy and adjuvant chemotherapy could be considered as one of feasible alternatives to primary radical surgery or concurrent chemoradiation therapy with the termination of pregnancy in pregnant women with FIGO stage IB cervical cancer who have two or more intermediate pathologic-risk factors.